2019
DOI: 10.1590/0004-282x20190076
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic motor neuronopathy and malignant acanthosis nigricans

Abstract: A 40-year-old woman presented with rapidly progressive quadriparesis and severe weight loss. Examination disclosed global amyotrophy, absent deep tendon reflexes and malignant acanthosis nigricans ( Figure). Neurophysiologic studies disclosed pure motor neuronopathy. Paraneoplastic screening with fullbody CT/MRI scan revealed an intravesical mural lesion (Figure) and urethrocystoscopy showed low-grade papillary urothelial carcinoma of the urinary bladder. High-titer serum anti-Hu antibodies were identified. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Usually, AN becomes the only clue for a hidden malignancy, and the oral region is usually involved [ 181 , 182 ]. Although the dermatological lesion itself does not display a malignant profile, it behaves similar to a paraneoplastic syndrome [ 183 , 184 , 185 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, AN becomes the only clue for a hidden malignancy, and the oral region is usually involved [ 181 , 182 ]. Although the dermatological lesion itself does not display a malignant profile, it behaves similar to a paraneoplastic syndrome [ 183 , 184 , 185 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wollina U. et al introduced the idea that AN is like a “two-sided coin”, being either related to IR-MS or malignancies [ 183 , 184 , 185 , 186 ]. A patient with AN may experience this skin lesion while appearing asymptomatic or already under surveillance for IR-related components.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only seven cases of AN have been reported in the English literature as summarized in Table 1. [5][6][7][8][9][10][11] However, there have been no such cases reported within China. Following this diagnosis, the patient was transferred to the Oncology Department for systematic chemotherapy.…”
Section: Dovepressmentioning
confidence: 99%
“…2,18 An additional case of all 3 paraneoplastic conditions was reported in the setting of metastatic cervical cancer (HPV positive). 19 Per a recent case report and literature review, 20 there have only been 8 cases of acanthosis nigricans reported in bladder transitional cell carcinoma, [20][21][22][23][24][25][26][27] half of which have included oral malignant acanthosis nigricans. [20][21][22][23] Only one report of concurrent cutaneous and oral malignant acanthosis nigricans and triple palms in the setting of bladder cancer has been reported.…”
mentioning
confidence: 99%